Comparing the impact of hip thrust versus squat training on lower limb performance in sub-elite athletes: a systematic review and meta-analysis - Asghari, S. H.; Wong, A.; Comfort, P.; Mirghani, S. J.; Sharifian, S.; Ghaderi, M. (Sports Biomechanics, 2025)
The aim of this systematic review and meta-analysis was to compare the effects of squat (SQ) and hip thrust (HT) training on performance in lower body athletic tasks, across different groups. A comprehensive search was conducted up to 31 May 2024, using PubMed, Web of Science, Scopus, Google Scholar, and Embase. SQ training was found to significantly improve vertical jump height (VJH) but greater than the HT. Neither SQ nor HT training had a significant impact on horizontal jump distance (HJD), short sprint time (SST), short sprint performance (SSP) or change of direction (COD) performance. In 12 to 16 sessions subgroup, SQ training significantly improved VJH, showing a medium ES. However, in other subgroups, neither SQ nor HT exercises produced significant improvements in HJD, SSP, SST, or COD performance. Subgroup analyses corroborated these findings. Squat exercises are more effective in developing VJH, while alternatively, no conclusive preference can be made between the exercises for enhancing HJD, SSP, and SST markers. Neither exercise had a discernible impact on COD performance. Future research should focus on conducting higher-quality studies to better elucidate the specific effects of SQ and HT training, or a combination of the two exercises, on various performance metrics.